2021
DOI: 10.1155/2021/1294410
|View full text |Cite|
|
Sign up to set email alerts
|

Additional Benefits Conferred by Endoscopic Sclerotherapy to Liver Cirrhosis Patients Receiving Endoscopic Variceal Ligation

Abstract: Objective. Gastroesophageal varices are a direct consequence of portal hypertension in cirrhosis. The management of gastroesophageal varices has evolved over the last decade resulting in reduced mortality and morbidity rates. The study was aimed to analyze the short-term and long-term efficacy of different endoscopic methods in the treatment of gastric varices in cirrhotic patients. Methods. From January 2016 to December 2019, 135 patients with liver cirrhosis and gastric varices undergoing different endoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%